CHANGES IN HAEMATOLOGICAL AND BIOCHEMICAL PARAMETERS IN RAM LAMBS FED ON HORSE GRAM TANNINS AND PROBIOTIC SUPPLEMENTATION DIETS - Parthasarathi, T.; Candra, A. Sarat; Raman, D.B.V. (Indian Journal of Animal Production and Management, 2017)
An experiment was conducted to study the effect of probiotics supplementation and tanniferous dietinclusion on health status by estimating the hematological and biochemical diagnostic parameters inDeccani ram lambs. 18 Deccani ram lambs of uniform body weight (16.5Â±0.64 kg) were randomly allottedto 3 groups in a completely randomized design. The dietary treatments were viz., T1: Basal diet (choppedsorgum stover + chopped green fodder as roughage source) + group 1 concentrate, T2: Basal Diet + Group2 concentrate (with horse gram), T3: Basal diet + Group 3 concentrate supplemented with probiotics @4kg per100kg concentrate. Deccani ram lambs were fed the respective diets ad lib. to meet the nutrientrequirements throughout 90 days of feeding trial. Blood glucose concentration was comparable among theexperimental groups, however relatively higher (P